Pattern and Management of Maxillofacial Injuries in Polytrauma Patients attending a Tertiary Care Hospital of Bangladesh (Update Dental College Journal, 2025)
Introduction: Treating maxillofacial injury, either minor or severe, in polytrauma patients, relies on initial resuscitation of the patient. Managing such cases requires prior knowledge of the pattern and severity of traumas. As there is inadequate baseline data for Bangladeshi population, the present study aimed to analyze the pattern and management of maxillofacial injuries in polytrauma patients attending a tertiary healthcare center in Bangladesh. Materials and methods: This was a cross-sectional observational study, conducted for six-month period from May 2021, in Chittagong Medical College Hospital, Chattogram. For this study 102 patients were selected purposively. Data were collected using a structured case record form. Results: Participants’ ages ranged from 4 to 68 years. Among the patients, 47.06% had concomitant injuries in the upper and lower extremities, followed by ‘head and extremity injury’ (25.49%). Mandible was the most common site for maxillofacial injuries. Mandibular fractures were the most common type of fractures (84.31% of multiple response cases). Among all facial fractures, single maxillofacial-region-fracture (62.75%) was more common than multiple such fractures (37.25%) in the polytrauma cases. Majority of maxillofacial-region-fractures (66.67%) were treated with closed reduction. Conclusion: Considering the site and pattern of maxillofacial injuries are needed for effective management to restore function and to minimize complications. For better patient support, emphasize should be given for multidisciplinary approach for development and allocation at tertiary care setting.Update Dent. Coll. j: 2025; 15(1): 15-19